The prognostic significance of LncRNA BLACAT1 overexpression in various tumors: a meta-analysis - Yan, Xuefen; Zhang, Nana; Wang, Gang; Wang, Jiaheng (Frontiers in Genetics, 2024)
Objective: Recent studies have revealed increasing evidence that the long non-coding RNA bladder cancer associated transcript 1 (LncRNA BLACAT1) plays an essential role in the emergence of different malignancies. This meta-analysis aimed to evaluate the prognostic significance of LncRNA BLACAT1 in various cancers. Methods: Six electronic databases (PubMed, Embase, Medline, Web of Science, China National Knowledge Infrastructure (CNKI), and the Chinese WanFang database) were comprehensively searched for relevant studies. The analysis of overall survival (OS) and clinicopathological characteristics was conducted. Results: Nineteen studies with 1559 patients were eventually eligible to be included in this meta-analysis. High expression level of LncRNA BLACAT1 was identified to be linked with shorter OS (HR:2.02, 95%CI:1.66-2.46, P＜0.001) and PFS (HR:2.424, 95%CI:1.827-3.020, P＜0.001) in cancer patients as opposed to low expression levels. Subgroup analysis showed that analysis model (multivariate or univariate), cut-off value (mean or median), sample size (more or fewer than 100), and cancer type had little effect on OS in multiple tumors. Moreover, high LncRNA BLACAT1 expression was associated with positive lymph node metastasis (HR:2.29, 95%CI:1.66-3.16, P<0.00001), advanced clinical stage (HR:2.29, 95%CI:1.65-3.19, P<0.00001) and worse differentiation status (HR:0.58, 95%CI: 0.37-0.92, P=0.02), compared to low LncRNA BLACAT1 expression. Conclusion: The findings highlight that high LncRNA BLACAT1 expression might be detrimental and induce a worse prognosis for cancer patients.